(untitled) (Innovaciones Educativas, 2021)
This essay proposes the analytical reading of the role played by the theoretical-methodological decisions of the teaching staff in the selection and appropriation of digital technologies in didactic interventions. Basically, the concept of “technological sovereignty” is highlighted in educational processes, in which the role of teachers is crucial to favor frameworks of “free paradigms” in technology, in teaching and learning. A conceptual journey is travelled based on the idea of “content curator”, based on the role of the person who teaches and the accent is placed on the notion of digital media in educational settings. Within the referential frameworks on technological freedom, two perspectives are proposed: “Free Software” and “Open Educational Resources”, as promoters of the construction of technological sovereignty within the didactic constructions, which are displayed in the spaces that they configure the teaching praxis. Ultimately and briefly, the essay is concluded by reflecting on the preponderant place that the teacher must assume who selects and combines educational materials in their didactic constructions.